A pH-responsive assembly based on upconversion nanocrystals and ultrasmall nickel nanoparticles. Issue 37 (11th September 2017) - Xu, Xia; Long, Yan; Lei, Pengpeng; Dong, Lile; Du, Kaimin; Feng, Jing; Zhang, Hongjie
Abstract : A hybrid assembly based on NaYF4 :Yb 3+, Er 3+ /Tm 3+ @NaYF4 (core@shell) upconversion nanocrystals and ultrasmall Ni nanoparticles (abbreviated as core@shell@Ni) for rapid response towards pH in different PBS solutions. Abstract : We report a hybrid assembly based on NaYF4 :Yb 3+, Er 3+ /Tm 3+ @NaYF4 (core@shell) upconversion nanocrystals and ultrasmall Ni nanoparticles (abbreviated as core@shell@Ni) for rapid response towards pH in different PBS solutions. In this approach, Ni nanoparticles located on the surface of the core@shell upconversion nanocrystal serve as an efficient quencher for upconversion luminescence (UCL). A series of dynamic processes of the 4 S3/2 → 4 I15/2 transition of Er 3+ in Er 3+ -doped core@shell@Ni have been presented in order to discuss the energy transfer mechanisms between UCNPs and Ni nanoparticles. The upconversion luminescence can be recovered by incubating the core@shell@Ni assembly with pH 5.0 PBS that oxidizes Ni to Ni 2+, while the UCL could be still quenched when the hybrid assembly was incubated with pH 7.4 PBS. However, the core@shell@Co assembly's response toward pH is not distinguished due to the rapid recovery of emission intensity both in pH 5.0 and 7.4 PBS. The ability of the core@shell@Ni assembly to distinguish different pH values may be a fine platform for the real-time optical monitoring of chemical reactions and many important physiological processes associated with pH.